Continuidade e/ou ruptura: a reforma gerencial da administração pública brasileira na era Lula - Forgiarini, Giorgio (2013)
It is intended with this paper to treat about the standard of rationality embedded to the Brazilian Public Administration by the management reform, started by the President Fernando Henrique Cardoso, and especially to treat about its continuation whether or not during the mandates of his opponent and successor, Luiz Inácio Lula da Silva (2003-2005 and 2006-2009). For drawing up the study, firstly, it was outlined, from the method of literature review, a foreshortened history about the different standards of rationality prevailing in different periods of the Brazilian Republic, from the patrimonial model characteristic of the Empire and first Republic (oligarchy) times, through the bureaucratic pattern opened in Brazil in the 1930s at the government of Getúlio Vargas, until the first movements towards reform of the Brazilian Public Administration management. Subsequent to this, it was analyzed the concepts of rationality starting from the theoretical and doctrinarian bias, by taking up base those ones established by Max Weber, differentiating the rationality concerning the ends (zweckrational), regarding the values of rationality (wertrational). In the same way, standards of rationality applied to management and bureaucratic models of public administration were analyzed theoretically, to from then, objectively define premises and assumptions that guide and define them. Further, the movements were addressed during the FHC government beginning to introduce new paradigms for Brazilian Public Administration and, finally, it was analyzed the measures and postures adopted by President Lula regarding the Brazilian Public Administration after his rise to power, for, in the light of objective data and theoretical concepts launched in the dissertation, completed by relative continuity and to some extent, afraid about the management reform during the mandates of President Lula.